Pharmacological Effect of Gracilaria corticata Solvent Extracts against Human Pathogenic Bacteria and Fungi - Kolanjinathan, K. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTThe present study was conducted to screen the pharmacological activity of Gracilaria corticata solvent extracts against human pathogenic bacteria and fungi. The seaweed, Gracilaria corticata was collected and powdered. The powdered material was extracted using the organic solvents viz., Methanol, Acetone, Chloroform, Hexane and Ethyl acetate. Antimicrobial activity of Gracilaria corticata solvent extract was determined by Disc diffusion method. Among the solvents tested, methanol extract of Gracilaria corticata showed maximum inhibitory activity than other solvents. The zone of inhibition of Gracilaria corticata methanol extract against bacteria was maximum against Gram positive cocci Streptococcus pyogenes followed by Bacillus subtilis, Staphylococcus aureus, Streptococcus epidermis and Bacillus cereus. For Gram negative bacteria, the maximum zone of inhibition was recorded in methanol extract of Gracilaria corticata against Klebsiella pneumoniae followed by Enterobacter aerogenes, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli and Vibrio cholerae. The minimum inhibitory concentration (MIC) values of Gracilaria corticata against bacteria was ranged between 1.25 to 80 mg/ml. For fungi, the zone of inhibition was maximum against Aspergillus flavus followed by Aspergillus fumigatus, Aspergillus niger, Candida albicans, Candida glabrata and Saccharomyces cerevisiae. The minimum inhibitory concentration (MIC) value of Gracilaria corticata against fungi was ranged between 2 mg/ml to 16mg/ml